Multiagent Coordination Using Probability Collectives - Mohamed, Lutfia Khalifa Haj (Eastern Mediterranean University EMU, 2017)
This thesis motivates and describes the use of probability collectives (PC) with a multiagent coordination system to solve different problems. The main challenge was to enable the agents to work in a coordinated way, optimizing the local utilities and contributing the maximum or minimum towards optimisation of a global objective. The approach was validated solving numerical benchmark problems such as sphere function in which the coupled variables are seen as autonomous agents working collectively to achieve the optimum solution. Moreover, PC algorithm solved successfully repeated games such as prisoner‟s dilemma, stag hunt, the battle of sexes game and choose sides. In all experimental trials, the optimum results were obtained at a reasonable computational cost. Keywords: Probability Collectives, Collective intelligence, Multiagent systems, Game theory.

ÖZ: Bu tez farklı problemleri çözmek için olasılık derlemelerinin (PC) çok ajanlı koordinasyon sistemi ile kullanımını motive eder ve açıklar. Ana zorluk, ajanlarin koordineli bir şekilde çalışmasını sağlamak, yerel memniyetin en iyilenmesini sağlamak ve küresel bir hedefin maksimize edilmesine katkıda bulunmaktır. Bu yaklaşım in başarimi değişkenlerin, en iyi çözümü elde etmek için birlikte çalışan özerk ajanlar olarak görülen küre işlevleri gibi sayısal karşılaştırma problemlerini çözerek gösterilmiştir. Buna ek olarak, PC algoritması esirlerin ikilemleri, haydut avı, cinsiyetler savaşı gibi tekrarli oyunlarda en iyi stratejilerin bulunmasi icin kullanildi. Tüm deneysel denemelerde, en iyi sonuçlar makul bir hesaplama maliyetiyle elde edilmiştir. Anahtar Kelimeler: Olasılık Kolektifleri, Kollektif Zeka, Çok ajanli Sistemler, Oyun Teorisi.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2017. Supervisor: Assist. Prof. Dr. Adnan Acan.
Keywords: Probability Collectives; Collective intelligence; Multiagent systems; Game theory; Computer Engineering; Multiagent systems - Computational intelligence